The Political Economics of Higher Education Finance for Mobile Individuals - Silke Übelmesser; Rainald Borck; Martin Wimbersky (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study voting over higher education finance in an economy with two regions and two separated labor markets. Households dffer in their financial endowment and their children's ability. Non-students are immobile. Students decide where to study; they return home after graduation with exogenous probability. The voters of the two regions decide on whether to subsidize higher education costs or whether to rely on tuition fees only. We find that in equilibrium, in both regions a majority votes for subsidies when the return probability is suffi ciently small. When that probability is large, both regions opt for full tuition finance. Interestingly, the higher the return probability, the smaller are the equilibrium subsidy rates, but the larger are the numbers of exchange students.
Keywords: H52; H42; D72; 330